The Influence of Picture Book to the Storytelling skill of Preschool Children - Ratnasari, Eka Mei (Universitas Negeri Semarang, 2020)
The benefit of storytelling activity to children’s skill development is to provide a positive contribution to children’s language skill. This research aimed to determine the impact of the picture book to the storytelling skill of children aged 4-5 years. The research subjects consisted of two kindergartens in Yogyakarta (Pringwulung and Cempaka kindergarten) Indonesia. The participants are 40 children. The data were used quasi-experimental research design. The research data obtained were analyzed with t-test through SPSS 16 program to see the differences between the experimental group and the control group. The result of this research was a significant influence of using picture book on the storytelling skill of preschool children. The recommendation from the result of this research was provided to parents and teachers particularly to develop children’s communication skill and practitioner in the discussion that especially emphasized addressing the need to increase opportunities for storytelling skill of preschool children in good stimulation.